Determination of in situ ruminal crude protein and starch degradation values of compound feeds from single feeds. Issue 5 (3rd September 2019) - Grubješić, Goran; Titze, Natascha; Krieg, Jochen; Rodehutscord, Markus
ABSTRACT: Dairy cows are commonly fed compound feed concentrates, whose accurate formulation relies on the additivity of ruminal degradation characteristics of single feeds, and the absence of associative effects. The main aim of this study was to evaluate the additivity of single feeds in compound feeds made thereof. Twelve single feeds were used to produce eight compound feeds in mash and pelleted form. Samples of single and compound feeds were incubated in situ in three ruminally fistulated dairy cows, and effective ruminal degradation (ED) of CP and starch (ST) was computed. The ED values of examined compound feeds could be, in most cases, accurately calculated from ED values of single feeds. Observed EDCP values were significantly lower than that calculated, but differences were overall small and not exceeded 5% points. No significant differences were observed between calculated and observed EDST. The study also examined the effects of pelleting of compound feeds on in situ degradation. Pelleting significantly increased EDCP (up to 8% points), and EDST (up to 4% points) of most compound feeds. This could have been caused by the pelleting process increasing the proportion of fine feed particles with fast disappearance from the bags. It was concluded that small associative effects between the examined single feeds could be disregarded when formulating compound feeds for dairy cows, and that additivity of EDCP and EDST can be assumed in most cases.